Entre imagens de afirmação e silêncios: um estudo sobre a branquitude nas obras didáticas de História - Lourenço, Mayra Oliveira (2023)
The present research aims to investigate how high school history textbooks contribute to the construction of a white identity. Through a quantitative and qualitative examination of the images selected to compose these works and an exploration of the contexts in which white identity is nominally evoked, the analysis seeks to assess to what extent these materials contribute to the development of a supposedly universal white identity that remains undescribed and privileged by the inequalities imposed by racism. White identity is depicted in numerous images portraying a wide range of situations, yet never as an oppressor; instead, it assumes an ethnic rather than a racial stance toward inequalities. By comparing the process of racialization in Brazilian and international contexts, the study points out similarities in the invisibility of violence perpetrated by white elites and the glorification of white figures within the contexts of articulation and struggles of black populations. Additionally, it underscores that the identification of white power is more explicit in the scenarios of the USA and South Africa. In the specifically Brazilian context, there is a promotion of miscegenation as a historical hallmark, obscuring racial inequalities by emphasizing class differences without explicitly designating the elites as white. Rather, the term is employed in situations where whites, blacks, and indigenous individuals share experiences of poverty, creating the illusion of racial harmony and peaceful alliance, akin to a notion of racial democracy